"In-Situ" Joint Preparation Technique for First Metatarsophalangeal Joint Arthrodesis: A Retrospective Comparative Study with "Flat-Cuts" Technique. Issue 1 (January 2022) - Prat, Dan; Pridgen, Eric; Lee, Wonyong; Wapner, Keith L.; Chao, Wen; O'Connor, Kathryn; Farber, Daniel C.
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: The most common joint preparation techniques mentioned in literature for 1st metatarsophalangeal (MTP) joint arthrodesis are 'cup and cone' and 'flat-cuts'. A third option of an 'in-situ' technique, has rarely been studied. This study compares the clinical, radiographic, and patients-reported outcomes of 'in-situ' joint preparation with a traditional 1st MTP joint preparation technique. Methods: The 'in-situ' technique utilizes the same dorsal surgical incision as traditional techniques. Cartilage and osteophyte removal are carried out using standard techniques without the use of specific reamers or a sagittal saw. The arthrodesis is performed in-situ with the similar freedom of joint positioning as the cup and cone technique, and traditional fixation constructs are applied. In this study, A retrospective chart review was performed for patients who underwent 1st MTP joint arthrodesis between January 2015 and December 2019. The complication, revision and non-union rates were examined in a multivariable logistic regression model. Patient reported outcome were analyzed in a repeated measures general linear model. Analysis of variance and Receiver Operating Characteristic were used to assess radiographic measurements. Results: Total of 388 1st MTP joint arthrodesis cases were included. Overall, 262 'Flat-Cuts' and 126 'In-Situ' cases were analyzed. Mean follow-up time was 292 days (median 174, SD 305). Joint-preparation technique did not have statistically significant impact on union rates (p=0.311) or revision rates (p=0.898). Diabetes-Mellitus was the most powerful predictor of non-union (p<0.001, OR 6.558, 95% CI: 2.534-16.969) and revision (p=0.02, OR 3.662, 95% CI: 1.230-10.905). The rate of transfer- metatarsalgia was significantly higher in 'flat-cuts' (p=0.015, OR 6.808, 95% CI: 1.460-31.744). Visual-Analogue-Scale and PROMIS- CAT-Physical significantly improved at 6-weeks, 3-months, and at last follow-up in both techniques (p<0.001, p=0.001), and the improvement was comparable between the techniques (p=0.078, p=0.100).'In-situ' technique resulted in significantly less mean 1st- ray shortening (3.05mm vs 7.64mm, p<0.001). In a Receiver-Operating-Characteristic analysis of transfer metatarsalgia and 1st ray shortening, the optimal diagnostic cut-off was 6.87 mm (LR 1.67, AUC 0.652, p=0.005, 95% CI: 0.56-0.74). Conclusion: 'In-situ' joint preparation technique is a simple, safe, and cost-effective technique for 1st MTP joint arthrodesis. In our series, 'in-situ' technique had a similar or better complication profile than the 'flat-cuts', while providing similar patient- reported outcomes. 'In-situ' technique resulted in significantly less 1st ray shortening, which was a predictor of transfer metatarsalgia.